2021
DOI: 10.3390/cancers13236067
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Engaging Immunotherapies, Highlighting Chimeric Antigen Receptor (CAR) T Cell Therapy

Abstract: In the past decade, chimeric antigen receptor (CAR) T cell technology has revolutionized cancer immunotherapy. This strategy uses synthetic CARs to redirect the patient’s own immune cells to recognize specific antigens expressed on the surface of tumor cells. The unprecedented success of anti-CD19 CAR T cell therapy against B cell malignancies has resulted in its approval by the US Food and Drug Administration (FDA) in 2017. However, major scientific challenges still remain to be addressed for the broad use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 224 publications
(220 reference statements)
0
10
0
Order By: Relevance
“…Combinations of cytokines with monoclonal antibodies to tumor antigens, checkpoint inhibitors, vaccines, and cell-based therapies are being investigated in clinical trials ( Table 3 ). Moreover, autologous and/or allogeneic T cell products have been designed to express immunostimulatory cytokines in addition to CAR that direct them to tumor-associated antigens ( 102 104 ). A phase I clinical trial of ST-067, a recombinant human IL-18 engineered to abolish binding and neutralization of its activity by IL-18BP, has been initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of cytokines with monoclonal antibodies to tumor antigens, checkpoint inhibitors, vaccines, and cell-based therapies are being investigated in clinical trials ( Table 3 ). Moreover, autologous and/or allogeneic T cell products have been designed to express immunostimulatory cytokines in addition to CAR that direct them to tumor-associated antigens ( 102 104 ). A phase I clinical trial of ST-067, a recombinant human IL-18 engineered to abolish binding and neutralization of its activity by IL-18BP, has been initiated.…”
Section: Discussionmentioning
confidence: 99%
“… 174 While some of these clinical trials have shown promising outcomes in cancer patients, many other CAR T-cells targeting various antigens are currently under investigation. 175 , 176 The ongoing clinical trials around CAR T-cell therapy generally cover a wide range of production techniques, antigen targets, and cancer types, with a special focus on a variety of areas, including deeper investigation of current FDA-licensed CAR T-cell products, research into existing or new target antigens, and exploration of CAR T-cell-based combination therapies to improve efficacy and safety. 146 …”
Section: Ongoing Clinical Trials On Car T-cell Therapymentioning
confidence: 99%
“…The large success and progress of chimeric antigen receptor (CAR)-engineered T cells in cancer immunotherapy ( 73 ) boosted the development of CAR-NK cells, which are currently being tested in multiple clinical trials ( 14 , 14 , 74 ). Interestingly, CAR technology can be combined with CIML NK cells to further enhance their functionality.…”
Section: Cytokine-induced Memory-like (Ciml) Nk Cellsmentioning
confidence: 99%